Dieng Culture Festival: Media Komunikasi Budaya Mendongkrak Pariwisata Daerah - Kusumastuti, Retno Dyah; Priliantini, Anjang (Jurnal Studi Komunikasi, 2017)
Culture has a dominant role in supporting the tourism sector of a region.. Likewise with the District of Banjarnegara that embodies the vision and mission related to culture through the implementation of Dieng Culture Festival that crowned as one of the three most popular Indonesian cultural festivals in the world. Dieng Culture Festival which is full of cultural meaning as the essence of a cultural communication process. This qualitative research uses constructivism paradigm to give an overview of cultural meaning in Dieng Culture Festival series. Data to support this study were compiled from interviews with Dieng cultural activists and literature review. The result of this research is the whole series of events in Dieng Culture Festival communicating the Javanese culture in general with the added local wisdom of the typical Dieng community, which is influenced by the growing beliefs in the surrounding community.